2019
DOI: 10.1111/ejn.14495
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trait fear of pain on event‐related potentials during word cue presentations that signal potential pain

Abstract: People who are especially afraid of pain may display attention biases that increase their risk for developing chronic pain following an injury. However, specific neurophysiological mechanisms underlying associations between elevated trait fear of pain levels and environmental cues that signal potential pain experiences are not well understood. To address this gap, event‐related potentials (ERPs) were recorded among 39 high pain‐fearful (H‐FOP) and 36 low pain‐fearful (L‐FOP) adults exposed to potentially painf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 84 publications
(135 reference statements)
0
6
0
Order By: Relevance
“…For the late segments of LPP (500–800 ms), only the main effect (group and load) was constantly found. Usually, LPP amplitudes linked to task demands such as evaluation, memory encoding, and affect regulation (Zheng, Lyu, & Jackson, 2019). This study revealed that the LPP amplitudes were affected by not only loads, which was consistent with the research mentioned above, but also pain.…”
Section: Discussionmentioning
confidence: 99%
“…For the late segments of LPP (500–800 ms), only the main effect (group and load) was constantly found. Usually, LPP amplitudes linked to task demands such as evaluation, memory encoding, and affect regulation (Zheng, Lyu, & Jackson, 2019). This study revealed that the LPP amplitudes were affected by not only loads, which was consistent with the research mentioned above, but also pain.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Wang et al [ 25 ] showed that painless subjects with high FOP had higher gray matter volumes in brain regions involved with pain sensations and fear processing, so they were more likely to perceive pain and fear. Furthermore, some laboratory studies have shown that FOP can predict pain perception and the rate of acute pain resolution in painless samples [ 12 , 26 , 27 ]. The outcomes of our study are aligned with these aforementioned conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Babel [ 2 ] previously reported that pain intensity can be predicted by state anxiety and trait pain anxiety. Similarly, Zheng et al [ 27 ] conducted a clinical study that showed that trait FOP increases sensitivity to pain cues. However, despite these important conclusions on our studied phenomenon, the association between trait FOP and state FOP has not effectively explained yet.…”
Section: Discussionmentioning
confidence: 99%
“…While the first period of significance falls right into the N2 component time‐window described in the literature (Garcia‐Larrea et al, 2003; Kakigi et al, 2004), it occurred slightly earlier than the POI we found (i.e., 408–500 ms; see Section 3.5). Regarding the second significant period, it is most likely related to the late segment of the late positive potential (LPP) component that Wang et al (2020) hypothesized to index processes such as evaluation, memory and affect regulation (Zheng et al, 2019). Yet, based on the results of the global duration statistics, such short‐lasting significant time‐period (respectively 12 and 27 ms) should rather be considered as false positives than as potential indicators of true effects.…”
Section: Exploratorymentioning
confidence: 99%